A Comparison of Methods for Assessing Situation Awareness in Current Day and Future Air Traffic Management Operations: Graphics-Based vs Text-Based Online Probe Systems. Issue 19 (2016) - Strybel, Thomas Z.; Chiappe, Dan; Vu, Kim-Phuong L.; Miramontes, Adriana; Battiste, Henri; Battiste, Vernol
Abstract: Operator situation awareness can be measured by examining operator response time and accuracy to online queries or probes. We compared an existing, text-based query method with a new graphics-based method. The text-based method presented multiple-choice queries to air traffic controllers (ATCos) on a display next to the DSR. Responses were entered by selecting one of the response alternatives presented with the query. The graphics-based method presented the query along with a screen shot of ATCo's current traffic on the DSR. The ATCo responded by touching the symbol of the aircraft that was the subject of the question. These methods were compared in a simulation involving student ATCos currently enrolled in an Aviation Sciences program.